Evolution of PEKK crystallization measured in laser sintering - Benedetti, L.; Brulé, B.; Decraemer, N.; Evans, K. E.; Ghita, O. (Frontiers in Manufacturing Technology, 2022)
The rising popularity of laser sintering (LS) technology has increased by the broadening of available materials for this process. Kepstan 6002 poly(ether ketone ketone)